An empirical vegetation correction for soil water content quantification using cosmic ray probes. Issue 4 (8th April 2015) - Baatz, R.; Bogena, H. R.; Hendricks Franssen, H.‐J.; Huisman, J. A.; Montzka, C.; Vereecken, H.
Abstract Cosmic ray probes are an emerging technology to continuously monitor soil water content at a scale significant to land surface processes. However, the application of this method is hampered by its susceptibility to the presence of aboveground biomass. Here we present a simple empirical framework to account for moderation of fast neutrons by aboveground biomass in the calibration. The method extends the N0‐calibration function and was developed using an extensive data set from a network of 10 cosmic ray probes located in the Rur catchment, Germany. The results suggest a 0.9% reduction in fast neutron intensity per 1 kg of dry aboveground biomass per m2 or per 2 kg of biomass water equivalent per m2. We successfully tested the novel vegetation correction using temporary cosmic ray probe measurements along a strong gradient in biomass due to deforestation, and using the COSMIC, and the hmf method as independent soil water content retrieval algorithms. The extended N0‐calibration function was able to explain 95% of the overall variability in fast neutron intensity.